(untitled) (Medical Forum Monthly, 2021)
Objective: To evaluate the expertise and infrastructure of addiction centers and drug rehabilitation programs in South Punjab, Pakistan. Study Design: A descriptive Cross – sectional study Place and Duration of Study: This study was conducted at the Multan Medical & Dental College, Multan from March 2020 – March 2021. Materials and Methods: This questionnaire has been formulated based on the quality parameters set by UNODC and includes various capacity domains including the facilities being offered, expertise available, policy making, audit protocols and infrastructure present in each facility. Data was collected from 18 addiction and drug rehabilitation centers from all across South Punjab, Pakistan. Results: Out of the 18 centers, 6 were private set-ups and 12 were government run. Sixty six percent of the centers offered inpatient admission services. The bed capacity varied from 10-100 beds across all centers and the average stay varied from 1 week to 3 months. Average cost for stay for private centers was 3000 PKR [19.15 ] per day [range: 9.57-63.8] whereas Government institutes charged standard fee of 200 PKR [1.28] per day. Only 39% of the centers had a psychiatrist or addiction specialist. Only 20% had a sociological officer. All the centers reported doing symptomatic management. No center reported using tapered dose regimen for Alcohol and BDZ detoxification or using Buprenorphine or Methadone for Opioid withdrawals. Conclusion: This is the first of its kind of study to evaluate the drug treatment and rehabilitation centers of South Punjab, Pakistan in terms of infrastructure and expertise. The authors found vacuums in the current practice especially regarding the absence of psychiatrist or addiction specialist in many of these centers and noncompliance with any international guidelines as well as the high cost of treatment in private setups which is also an area of concern.